Foreign Direct Investment on Improving The Quality of Exported Commodities in Indonesia Manufacture Sector - Siregar, Dolly Poncho (CV. Ridwan Publisher, 2020)
This paper uses the theoretical framework of Melitz type where the model explains the heterogeneity within the firms and the significance of the inwards Foreign Direct Investment on the improvement of export quality. FDI will affect optimal prices and quality. The theoretical model then transformed into panel data with the industry level data in Indonesia’s manufacturing sector from 2011 to 2015. The finding estimated is there is a significant impact of Foreign Direct Investment on the quality of commodities exported which is increasing in Foreign Direct Investment increase the export unit value.